Supporting Young Children’s Social–Emotional Wellbeing in Early Childhood Education and Care: Perspectives from the Sector - Lisa Murray; Penny Levickis; Laura McFarland; Patricia Eadie; Lynn Lee-Pang; Jon Quach; Jane Page (Education Sciences)
Child wellbeing and mental health continues to be a significant public health issue, particularly in the wake of the COVID-19 pandemic. Early childhood education and care (ECEC) professionals are uniquely positioned to monitor and support young children’s wellbeing and can thus provide important insights to inform early interventions and support. This qualitative study sought to explore Australian ECEC professionals’ perspectives about supporting young children’s social–emotional wellbeing in early learning settings. Twenty participants participated in six online focus groups, with five key themes conceptualised from the data: (1) escalation in child and educator wellbeing needs; (2) discrepancies in educator experience and skills; (3) access to high-quality professional development; (4) prioritising relationships and continuity of care; and (5) nurturing children’s agency, identity, and belonging. The findings encompass concerns about children’s wellbeing and educators’ capacity to support it, as well as suggested strategies to strengthen the support for children’s wellbeing in early learning settings. The implications of the study findings are discussed.